Uji Efektivitas Bioinsektisida Beauveria Bassiana Bals, Vull. (Bassikoka) Terhadap Larva Instar III Spodoptera Litura Pada Tanaman Sawi (Brassica Juncea L.) - Marlina, Wa Ode; Goo, Nureny; Noya, Sartjee H (Jurnal Agrosilvopasture-Tech, 2023)
This study aims to obtain data on the effectiveness of several concentrations of Beauveria bassiana (BASSIKOKA) against the third instar pest Spodoptera Litura on mustard greens. This research was conducted at the Laboratory of Pests, Faculty of Agriculture, University of Pattimura. This study used a completely randomized design with Beauveria bassiana (Bassikoka) bioinsecticide treatment with a concentration of 0.1g/L of water, 0.2g/L of water, 0.3 g/L of water, 0, 4 g/L, and control as comparison. Observations were made on the initial symptoms of infection, mortality, and the fastest time to kill 50% of the third instar larvae of Spodoptera litura. Based on the results of the study, it can be concluded that the concentration of 0.4 g/L bioinsecticide Beauveria bassiana (Bassikoka) is effective against third instar larvae of Spodoptera litura L. with a mortality rate of 90% and the fastest time to kill 50% of third instar larvae of Spodoptera litura 2.4 days.